2021
DOI: 10.1107/s2052252521003882
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the self-association and desolvation in crystal nucleation

Abstract: As the first step in the crystallization process, nucleation has been studied by many researchers. In this work, phenacetin (PHEN) was selected as a model compound to investigate the relationship between the solvent and nucleation kinetics. Induction times at different supersaturation in six solvents were measured. FTIR and NMR spectroscopy were employed to explore the solvent–solute interactions and the self-association properties in solution. Density functional theory (DFT) was adopted to evaluate the streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…It is now clear that the higher attachment frequency in toluene, although nearly twofolds, than in ethanol or acetonitrile will be penalized by the creation of more than twofold greater size of the critical nucleus. In fact, several recent studies , have shown that the presence of hydrogen-bonded dimers in solution may not be necessary to accelerate crystal nucleation. For example, the nucleation of phenacetin in chloroform is the slowest among other solvents though the chloroform solution displays the presence of phenacetin dimer with the lowest solvation strength and highest attachment frequency .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clear that the higher attachment frequency in toluene, although nearly twofolds, than in ethanol or acetonitrile will be penalized by the creation of more than twofold greater size of the critical nucleus. In fact, several recent studies , have shown that the presence of hydrogen-bonded dimers in solution may not be necessary to accelerate crystal nucleation. For example, the nucleation of phenacetin in chloroform is the slowest among other solvents though the chloroform solution displays the presence of phenacetin dimer with the lowest solvation strength and highest attachment frequency .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several recent studies , have shown that the presence of hydrogen-bonded dimers in solution may not be necessary to accelerate crystal nucleation. For example, the nucleation of phenacetin in chloroform is the slowest among other solvents though the chloroform solution displays the presence of phenacetin dimer with the lowest solvation strength and highest attachment frequency . The case, previously considered to be abnormal, can now be explained if one considered the trade-off between attachment frequency and size of the critical nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the density of high-order associates/aggregates (metastable clusters relative to bulk solution) is developed by molecular association/aggregation likely prior to their structure development in the pre-nucleation stage. The associates or aggregates as illustrated in the aforementioned systems bear the inevitable solvation effect [127,147], and desolvation of solvent molecules [148][149][150] accompanied by superamolecular reconstruction leads to the formation of a nucleus. Recent studies have revealed the detailed kinetics of orientated attachment and the importance of desolvation on particle aggregation during crystal nucleation [80,151].…”
Section: Aggregation-based Multiple Nucleation Pathwaysmentioning
confidence: 99%
“…Importantly, solubility plays a critical role in the selection of the crystallization method and crystallization conditions in the crystallization process . Moreover, different solvents have different interactions between solvents and solutes, which have an impact on the nucleation and growth kinetics. , Hence, choosing the appropriate concentration, solvents, and other operating conditions is helpful to obtain high-quality products.…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, different solvents have different interactions between solvents and solutes, which have an impact on the nucleation and growth kinetics. 4,5 Hence, choosing the appropriate concentration, solvents, and other operating conditions is helpful to obtain high-quality products.…”
Section: Introductionmentioning
confidence: 99%